Pengembangan Keterampilan Berwirausaha Siswa melalui Pelatihan Kewirausahaan Digital Berbasis Canva di SMK TI At-Taqwa - Astuti, Dwi; Fauziana, Eva; Anisa, Citra (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
This community service program aimed to enhance digital entrepreneurship skills among vocational high school students through practice-based UMKM training. The program was conducted at SMK IT Attaqwa 07, Sumber Jaya, Bekasi, involving approximately 30 students over a two-week period. The training activities included entrepreneurship seminars, Canva-based design workshops, product photography training, and direct product marketing practices. The results indicated a significant improvement in students’ competencies, and interest in starting their own businesses. The findings revealed an 85% increase in students’ understanding of digital entrepreneurship, 78% improvement in digital promotional design skills using Canva, and enhanced entrepreneurial motivation after participating in the training program. In addition, students successfully produced and sold products, which strengthened their practical business experience and communication skills. This program demonstrates that integrating digital technology and project-based learning effectively enhances entrepreneurial competence and motivation among vocational students. The findings suggest that such training models can be implemented more broadly to support the development of young entrepreneurs in the digital economy era.